Understanding Barriers to Engagement With a Prostate Cancer Research and Genetic Risk Service Among UK Men of Black African or Black Caribbean Ancestry - Hall Rose; Emma Hainsworth; Jeff Thompson; Saran Green; McGrowder Eva; James Denzil; Eeles Rosalind; Elizabeth Bancroft (Health Expectations, 2025)
ABSTRACT Introduction Prostate cancer is the second most common cancer worldwide, and there is no national prostate cancer screening programme in the United Kingdom. Men of African ancestry are twice as likely to be diagnosed as men of European ancestry and are diagnosed at a younger age. Despite this, Black men are under‐represented in seeking advice about prostate cancer symptoms, screening and genetic research. There is increasing research focused on targeted prostate cancer screening, using genetic testing to guide screening by identifying those at highest risk, but this could only be considered if people of all ethnicities would accept this approach. It is vital to diagnose prostate cancer early, when it is curable. We wanted to identify the barriers to engagement with prostate cancer genetic research to increase participation from those at highest risk. Methods We conducted two community discussion groups, each attended by 30–35 Black men and their families. We conducted interviews with three Black community champions who have a lived experience of prostate cancer. Thematic analysis was performed on the transcripts. We used a participatory approach to develop our themes with members of the community, two of whom are co‐authors on this paper. Results Themes were grouped as barriers or facilitators to engagement with prostate cancer genetic risk services. Barriers included GP reluctance to perform prostate‐specific antigen (PSA) testing, cultural inhibition around discussing prostate cancer and family history, fear of rectal examination, fear of cancer diagnosis and lack of trust in the healthcare system, no awareness about the role of genetics in prostate cancer risk assessment, negative connotations of genetic testing (e.g., genetic modification) and genetic data being used inappropriately. Facilitators were family and community support, the sharing of experiences, good communication with doctors, raised prostate cancer awareness, genetic risk assessment to guide the need for screening and facilitate early diagnosis, improving future outcomes for prostate cancer in the Black community through engaging with genetic research and assurance that there are regulations in place to protect genetic and personal data with guidance around when genetic results must be disclosed. Conclusions Understanding barriers and facilitators can guide recommendations for health services to improve access and uptake within the Black community and improve representation in genetic research. Better representation will support improvements in cancer outcomes and understanding of the genetic risk of prostate cancer in the Black community. Patient or Public Contribution We initially attended community prostate cancer awareness events to speak to members of the community. We established trusted and two‐way relationships with Black ‘community champions’ who lead support groups in the Black community and often have a lived experience of prostate cancer. We were invited to attend their support groups to deliver awareness talks and address concerns about prostate cancer risk and screening. We then conducted discussion groups and collected data. Our analysis was conducted in partnership with our community champions. Our findings are described in this paper, with their co‐authorship. We have also disseminated our findings in a co‐produced newsletter to feed back our findings to the community members, who gave us their time. We have also shared information at a stakeholder day, attended by 65 individuals from the community, where we also planned future work. We have reimbursed participants for their time, which is in line with NIHR guidance. As described above, patient and public involvement has been the guiding principle throughout this project.